INTEGRASI TEKNOLOGI DALAM PEMBELAJARAN: KAJIAN PEDAGOGI UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS - Ade Syarifudin; Nurdin; Sururi; Ady Akbar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The integration of technology in learning has increasingly developed as an instructional strategy that supports the mastery of 21st-century skills, particularly critical thinking skills. Although research on the use of educational technology continues to grow, there remains a need for studies that synthesize how technology is pedagogically integrated to develop learners’ critical thinking skills. This study aims to conduct a systematic review of research examining strategies for integrating technology in learning to enhance critical thinking skills. The method employed is a systematic review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Articles were retrieved from the Scopus, Web of Science, and Google Scholar databases, covering publications from 2020 to 2025. Through a rigorous selection process, 12 articles met the inclusion criteria and were qualitatively analyzed. The findings indicate that technology integration is effective in fostering critical thinking skills when implemented through pedagogically structured learning activities, such as problem-based learning, inquiry-based learning, collaboration, and reflection. Technologies that support visualization, simulation, interaction, and discussion encourage learners to engage in higher-order cognitive processes, including analysis, evaluation, and decision-making. However, the effectiveness of technology integration is strongly influenced by instructional design, the role of educators, and the implementation context. This review emphasizes that technology does not automatically enhance critical thinking skills but requires appropriate pedagogical integration to achieve meaningful learning outcomes.